Outcome and prognostic factors following palliative craniospinal irradiation for leptomeningeal carcinomatosis - El-Shafie, Rami; Kronsteiner, Dorothea; Uzun-Lang, Kristin; Schlaich, Fabian; Adeberg, Sebastian; Paul, Angela; Häfner, Matthias; Katayama, Sonja; Sterzing, Florian; Hörner-Rieber, Juliane; Löw, Sarah; Herfarth, Klaus; et al. (Cancer management and research, 2019)
Background: Leptomeningeal carcinomatosis (LC) is a severe complication of metastatic tumor spread to the central nervous system. Prognosis is dismal with a median overall survival (OS) of ~10-15 weeks. Treatment options include radiotherapy (RT) to involved sites, systemic chemo-or targeted therapy, intrathecal chemotherapy and best supportive care with dexamethasone. Craniospinal irradiation (CSI) is a more aggressive radiotherapeutic approach, for which very limited data exists. Here, we report on our 10-year experience with palliative CSI of selected patients with LC. Patients and methods: Twenty-five patients received CSI for the treatment of LC at our institution between 2008 and 2018. Patients were selected individually for CSI based on clinical performance, presenting symptoms and estimated benefit. Median patient age was 53 years (IQR: 45-59), and breast cancer was the most common primary. Additional brain metastases were found in 18 patients (72.0%). RT was delivered at a TomoTherapy machine, using helical intensity-modulated radiotherapy (IMRT). The most commonly prescribed dose was 36 Gy in 20 fractions, corresponding to a median biologically equivalent dose of 40.8 Gy (IQR: 39.0- 2.5). Clinical performance and neurologic function were assessed before and in response to therapy, and deficits were retrospectively quantified on the 5-point neurologic function scale (NFS). A Cox proportional hazards model with univariate and multivariate analyses was fitted for survival. Results: Twenty-one patients died and four were alive at the time of analysis. Median OS from LC diagnosis was 19.3 weeks (IQR: 9.3-34.0, 95% CI: 11.0-32.0). In univariate analysis, a Karnofsky performance scale index (KPI) ≥70% (P=0.001), age ≤55 years at LC diagnosis (P=0.022), cerebrospinal fluid (CSF) protein <100 mg/dL (P=0.018) and no more than mild or moderate neurologic deficits (NFS ≤2; P=0.007) were predictive of longer OS. So were the neurologic response to treatment (P=0.018) and the application of systemic therapy after RT completion (P=0.029). The presence of CSF flow obstruction was predictive of shorter OS (P=0.026). In multivariate analysis, age at LC diagnosis (P=0.018), KPI (P<0.001) and neurologic response (P=0.037) remained as independent prognostic factors for longer OS. Treatment-associated toxicity was manageable and mostly grades I and II according to the Common Terminology Criteria for Adverse Events v4.0. Eight patients (32%) developed grade III myelosuppression. Neurologic symptom stabilization could be achieved in 40.0% and a sizeable improvement in 28.0% of all patients. Conclusion: CSI for the treatment of LC is feasible and may have therapeutic value in carefully selected patients, alleviating symptoms or delaying neurologic deterioration. OS after CSI was comparable to the rates described in current literature for patients with LC. The use of modern irradiation techniques such as helical IMRT is warranted to limit toxicity. Patient selection should take into account prognostic factors such as age, clinical performance, neurologic function and the availability of systemic treatment options.